The Effect Of Teaching Style And Family Environment On Student Learning Outcomes In Journal Materials General Class XI AKL - Judika Nurhayani Situmorang; Roza Thohiri (Citakonsultindo, 2026)
The core problem in this research is the suboptimal student learning outcomes in accounting, specifically regarding general journal entry materials. This study aims to determine whether there is a positive and significant influence of Teacher's Teaching Style and Family Environment, both partially and simultaneously, on General Journal Learning Outcomes among 11th-grade AKL students at SMK Negeri 1 Medan. This research was conducted at SMK Negeri 1 Medan using a quantitative ex-post facto approach. The population as well as the sample in this study consisted of all 137 students of the 11th-grade AKL, selected using the total sampling technique. Data collection techniques involved documenting the Mid-Term Examination (UTS) scores and distributing closed-ended questionnaires with a 4-point Likert scale. The research instrument consisted of 28 statements: 18 items for Teacher's Teaching Style (X1) and 10 items for Family Environment (X2). The instruments were previously tested for validity and reliability. The collected data were processed using multiple linear regression analysis via SPSS version 25.0 software. The multiple linear regression analysis yielded the equation: Y = 27.654 + 0.426X_1 + 1.244X_2. Based on partial hypothesis testing (t-test), there is a significant positive influence of Teacher's Teaching Style on general journal learning outcomes with a t-value of 3.100 > 2.001 t-table and a significant value of 0.003 < 0.05. The Family Environment variable also partially exerts a significant positive effect on learning outcomes with a t-value of 4.781 > 2.001 t-table and a significant value of 0.000 < 0.05. Simultaneously (F-test), both independent variables significantly influence the dependent variable with an F-value of 41.761 > 3.153 F-table and a significant value of 0.000 < 0.05. The Adjusted R Square value indicates that the simultaneous contribution of these two independent variables is 57.6%, while the remaining 42.4% is explained by other external variables not examined in this study